Water-use accounts in CPWF basins: Simple water-use accounting of the Volta Basin - Kirby, M.; Condappa, D. de; Mainuddin, M.; Eastham, Judy; Thomas, M. (2010)
This paper apples the principle of west –use accounts, developed in the first of the series, to the Volta River in West Africa. The Volta Basin covers six countries, with 85% of its area in Ghana and Burkina Faso. Runoff in all three tributaries increases from 2-7% in the drier north to 12-26 % in the higher – rainfall south. Grassland is the dominant land use throughout Basin ranging from 76% of the Delta catchment in the south to 98% of the Arly catchment with corresponding water use of 55% and 92% of water used in each. Increasing irrigation in the basin of all three tributaries to about one-third of the land identified by FAO as potentially irrigable gives lower flows and storage in the Dam.